Kedudukan Anak Diluar Kawin Dalam Sistem Pewarisan Menurut Hukum Adat Di Bali - Anak Agung Sagung Laksmi Dewi; I Kadek Agus Sugiarta; i Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2025)
The presence of a child is happiness and prosperity for a family. However, the birth of a child from a woman who is not married or called a child outside of marriage causes many conflicts between families and communities regarding the status of the rights and responsibilities of children. This study aims to understand the role of unmarried children in the inheritance system and solutions to solve the problem of distributing inheritance of unmarried children in accordance with Balinese customary law. The normative legal approach is the methodology used in this study. Based on research and discussion, Balinese customary law culture recognizes that children born out of wedlock have the same status as legitimate children. Children out of wedlock have no legal relationship with their biological father, which leads to them having a lower status and fewer legal rights under customary law. They can still receive inheritances and gifts from their biological mother and father, but they also have responsibilities as heirs.